2015
DOI: 10.4103/0253-7613.165182
|View full text |Cite
|
Sign up to set email alerts
|

Structured oral examination in pharmacology for undergraduate medical students: Factors influencing its implementation

Abstract: Objectives:The study aims to understand the process and factors influencing the implementation of structured oral examination (SOE) for undergraduate medical students; in comparison with conventional oral examination (COE) in pharmacology.Methods:In a randomized, parallel group study, 123 students of pharmacology were divided into two groups, SOE (n = 63) and COE (n = 60). Students of each group were subdivided into two, and four examiners took viva voce individually. Three sets of questionnaires from autonomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Inclusion of MCQ in the teaching learning will help the student in PG entrance examination as a part of written test was suggested by the students. 10 As the students expressed the standard textbook as their important learning material in place of the lecture and class notes, teachers shall prepare lecture and class note exclusively to the points of examination and understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of MCQ in the teaching learning will help the student in PG entrance examination as a part of written test was suggested by the students. 10 As the students expressed the standard textbook as their important learning material in place of the lecture and class notes, teachers shall prepare lecture and class note exclusively to the points of examination and understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Oral examinations are an integral part of pharmacology assessment. In this context various factors influencing the implementation of Structured Oral Examinations (SOE) in Pharmacology has been discussed (Khilnani et al, 2015). In a randomized, parallel group, 2-arm study viz: SOE (n = 63) and Conventional Oral Examination (COE) (n = 60).…”
Section: Assessmentmentioning
confidence: 99%
“…2 Viva voce is an important format of assessment that allows probing of breadth and depth of the knowledge. 3 Joughin defined the viva examination as "assessment in which a student's response to the assessment task is verbal, in the sense of being expressed or conveyed by speech instead of writing." 4 Recent studies have shown that in its traditional mode it is riddled with flaws and might not be appropriate for the assessment of student's interactive skills and higher cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Obviously, to utilize this mode of evaluation more effectively, it requires reorientation and careful construction of questions to test higher cognitive domains. 3,13 In order to overcome, the biases in the conventional format of assessment, structured oral and practical examination has been formatted by various workers. 3,8,14 Nevertheless, this modified format of oral assessment may provide an equal opportunity to judge the knowledge and problem-solving ability of every student appearing in the exams, and therefore, may prove to be more reliable in terms of minimizing the bias and reducing the luck factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation